A comparative study of long-time series of global-scale albedo products. Issue 1 (31st December 2023) - Mengyao, Li; Qiang, Liu; Ying, Qu
ABSTRACT: Albedo is a key variable in the study of global or regional earth system models. High-quality albedo products are helpful for the accurate analysis and prediction of the Earth's environment and climate. This paper analyzes the similarities and differences in several global-scale albedo products. The conclusions are as follows: (1) Ignoring the downward radiation weight leads to a maximum deviation of ±0.2 in the mean albedo in space and time; (2) Most of the products have good consistency at the global scale, especially after 2000, the consistency in the middle latitudes is better than that in the low latitudes and high latitudes; (3) Although there are obvious inter-annual variations and zonal differences in global mean albedo data from 2000 to 2020, the overall trend is not significant. The complex spatio-temporal variation of albedo requires high-quality remote sensing products to characterize its details. However, existing datasets do not show good agreement in these details, and more efforts are needed in this area.